A new species of Trinibaculum (Monogenea: Dactylogyridae) parasite of the gills of Astyanax fasciatus (Cuvier, 1819) (Characiformes: Characidae) in a neotropical river, São Paulo state, Brazil - Narciso, Rodrigo Bravin [UNESP]; Brandão, Heleno [UNESP]; Yamada, Fábio Hideki [UNESP]; Benine, Ricardo Cardoso [UNESP]; Silva, Reinaldo José da [UNESP] (My University, 2014)
A new species of Monogenea - Trinibaculum pinctiarum n. sp. is described from the gills of Astyanax fasciatus known as "lambari do rabo vermelho", sampled in the Paranapanema River, Jurumirim reservoir, São Paulo State, Brazil. The new species is allocated to the genus Trinibaculum because it has a double ventral bar and dextro-lateral vagina. It is the second species (first species is Trinibaculum altiparanae) belonging to this genus that parasitizes the gills of the fish genus Astyanax. This monogenean is similar to T. altiparanae regarding the haptor structures and the bulbous distal vagina. However, Trinibaculum pinctiarum n. sp. differs in having: (1) coiled male copulatory organ, (2) accessory structure shaped as tweezers, (3) absence of postmedian process in the ventral bar, and (4) hooks with depressed thumb. The phylogenetic hypothesis of the genus Trinibaculum (Consistency index = 87%, Retention index = 80%, length = 16) based on 13 transformation series is (Trinibaculum rotundus, T. brazilensis, T. altiparanae, T. pinctiarum n. sp.). Such hypothesis corroborates current phylogenies of characiformes fishes. Moreover, this study includes a new identification key for the species of the genus Trinibaculum based in morphological characters.

Una nueva especie de Monogenea Trinibaculum pinctiarum n. sp. fue reportada parasitando las branquias de Astyanax fasciatus, conocido popularmente como "lambarí de rabo rojo", capturado en el río Paranapanema, reservatorio Jurumirim, São Paulo, Brasil. La nueva especie se asigna al género Trinibaculum por la presentación de una barra ventral doble y la apertura vaginal dextrolateral. Esta es la segunda especie, junto con T. altiparanae, perteneciente a este género que parasita las branquias de los peces del género Astyanax. Esta especie se parece con T. altiparanae en las partes del haptor y la presencia de la vagina distal con el bulbo, pero difiere por tener: (1) un órgano copulador masculino enrollado, (2) pieza accesoria en forma de pinza, (3) proceso posteroventral ausente en la barra dorsal, (4) ganchos con el pulgar deprimido. La filogenia hipotética de especies de Trinibaculum (Índice de Consistencia = 87%, Índice de Retención = 80%, longitud = 16) sobre la base de 13 series de transformación es (Trinibaculum rotundus (T. brazilensis (T. altiparanae, Trinibaculum pinctiarum n. sp.))). Esta hipótesis se corrobora con la actual filogenia de los peces characiformes. Además en este estudio se presenta una nueva clave de identificación para las especies del género Trinibaculum basada en caracteres morfológicos.
Una nueva especie de Trinibaculum (Monogenea: Dactylogyridae) parásito de las branquias de Astyanax fasciatus (Cuvier, 1819) (Characiformes: Characidae) en un río neotropical, estado de São Paulo, Brasil
Keywords: Astyanax fasciatus; Freshwater fish; Identification key; Paranapanema river; Phylogeny; Taxonomy; Trinibaculum pinctiarum n. sp.; Clave de identificación; Filogenia; Peces de agua dulce; Río Paranapanema; Taxonomía; Trinibaculum pinctiarum n. sp.